Proteolytic activity and reduction of gliadin-like fractions by sourdough lactobacilli - Rollan, Graciela Celestina (2005)
Aims: To characterize the peptide hydrolase system of Lactobacillus plantarum CRL 759 and CRL 778 and evaluate their proteolytic activity in reducing gliadin-like fractions. Methods and Results: The intracellular peptide hydrolase system of Lact. plantarum CRL 759 and CRL 778 involves amino-, di- (DP), tri- (TP) and endopeptidase activities. These peptidases are metalloenzymes inhibited by EDTA and 1,10-phenanthroline and stimulated by Co2+. DP and TP activities of Lact. plantarum CRL 759 and CRL 778, respectively, were completely inhibited by Cu2+. Lactobacillus plantarum CRL 778 showed the highest proteolytic activity and amino acids release in fermented dough. The synthetic 31-43 a-gliadin fragment was hydrolysed to 36% and 73% by Lact. plantarum CRL 778 and CRL 759 respectively. Conclusions: Lactobacillus plantarum CRL 759 and CRL 778 have an active proteolytic system, which is responsible for the high amino acid release during sourdough fermentation and the hydrolysis of the 31-43 α-gliadin-like fragment. Significance and Impact of the Study: This work provides new information of use when obtaining sourdough starters for bread making. Moreover, knowledge regarding lactobacilli capable of reducing the level of gliadin-like fractions, a toxic peptide for coeliac patients, has a beneficial health impact.